HUDUD DAN UNDANG-UNDANG JENAYAH SYARIAH DALAM KERANGKA PERLEMBAGAAN DAN SISTEM PERUNDANGAN "DUALISME": KOMITMEN PELAKSANAAN KE ARAH MEMBENDUNG JENAYAH DI MALAYSIA: Hudud and Shariah Criminal Offences within the Constitutional Framework and the "Dualism" Legal System: The Commitment towards Curbing Crimes in Malaysia - Ismail, Siti Zubaidah (Jurnal Syariah, 2014)
The issue of hudud has become a polemic among politicians and academics alike. Ongoing debates and discourses have been directly focused on the position of Islam in the Federal Constitution, the supremacy of the Constitution and how Islamic law was not adopted as the law of the land and its consequences on the separation of jurisdiction between federal and states. Within that framework, this article examines the position of hudud and shariah criminal offences in general and suggests a new dimension on how to look at hudud and not be intimidated by it. While the aspiration to implement an Islamic criminal law in toto is appreciated, one has to understand the nature and context of the country’s legal system to understand how Islamic criminal law can be implemented.